2022
DOI: 10.3390/metabo12100907
|View full text |Cite
|
Sign up to set email alerts
|

First Report on Comparative Essential Oil Profile of Stem and Leaves of Blepharispermum hirtum Oliver and Their Antidiabetic and Anticancer Effects

Abstract: The current research was designed to explore the Blepharispermum hirtum Oliver (Asteraceae) stem and leaves essential oil (EO) composition extracted through hydro-distillation using gas chromatography-mass spectrometry (GC-MS) analysis for the first time. The EOs of the stem and leaves of B. hirtum were comparatively studied for the in vitro antidiabetic and anticancer potential using in vitro α-glucosidase and an MTT inhibition assay, respectively. In both of the tested samples, the same number of fifty-eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Thus, our current findings agree with the data depicted by Rao et al [ 86 ] and Mahmoud et al [ 87 ], however, our results deviate from those as stated by Bansod et al [ 88 ], and Oumzil et al [ 89 ]. Different plant species vary in their chemical constituents, which can overcome various human health complications, as well as that the environmental gradients influence the bioactive constituents within a plant species, as earlier stated by Shah et al [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our current findings agree with the data depicted by Rao et al [ 86 ] and Mahmoud et al [ 87 ], however, our results deviate from those as stated by Bansod et al [ 88 ], and Oumzil et al [ 89 ]. Different plant species vary in their chemical constituents, which can overcome various human health complications, as well as that the environmental gradients influence the bioactive constituents within a plant species, as earlier stated by Shah et al [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…The predominant chemical in the EO from leaves was discovered to be 24-norursa-3,12-diene (9.08%), with caryophyllene oxide (5.62%), β-selinene (7.26%), β-eudesmol (7.81%), and thunbergol (5.84%) following closely. When B. hirtum was tested to acarbose, it was found that the stem had significantly more antidiabetic potential than the EO of the leaves [88].…”
Section: Blepharispermum Hirtum Essential Oilmentioning
confidence: 99%